Ain't but a few of us black music writers tell their story - Jenkins, Willard 1949- (Duke University Press, 2022)
Despite the fact that most of jazz's major innovators and performers have been African American, the overwhelming majority of jazz journalists, critics, and authors have been and continue to be white men. No major mainstream jazz publication has ever had a black editor or publisher. Ain't But a Few of Us presents over two dozen candid dialogues with black jazz critics and journalists ranging from Greg Tate, Farah Jasmine Griffin, and Robin D. G. Kelley to Tammy Kernodle, Ron Welburn, and John Murph. They discuss the obstacles to access for black jazz journalists, outline how they contend with the world of jazz writing dominated by white men, and point out that these racial disparities are not confined to jazz but hamper their efforts at writing about other music genres as well. Ain't But a Few of Us also includes an anthology section, which reprints classic essays and articles from black writers and musicians such as LeRoi Jones, Archie Shepp, A. B. Spellman, and Herbie Nichols.ContributorsEric Arnold, Bridget Arnwine, Angelika Beener, Playthell Benjamin, Herb Boyd, Bill Brower, Jo Ann Cheatham, Karen Chilton, Janine Coveney, Marc Crawford, Stanley Crouch, Anthony Dean-Harris, Jordannah Elizabeth, Lofton Emenari III, Bill Francis, Barbara Gardner, Farah Jasmine Griffin, Jim Harrison, Eugene Holley Jr., Haybert Houston, Robin James, Willard Jenkins, Martin Johnson, LeRoi Jones, Robin D. G. Kelley, Tammy Kernodle, Steve Monroe, Rahsaan Clark Morris, John Murph, Herbie Nichols, Don Palmer, Bill Quinn, Guthrie P. Ramsey Jr., Ron Scott, Gene Seymour, Archie Shepp, Wayne Shorter, A. B. Spellman, Rex Stewart, Greg Tate, Billy Taylor, Greg Thomas, Robin Washington, Ron Welburn, Hollie West, K. Leander Williams, Ron Wynn